Analisis Kualitas Layanan Sistem Akademik Terpadu Universitas Al Washliyah (SATUVA) Terhadap Kepuasan Dan Productivity Pengguna Menggunakan Metode End-User Computing Satisfaction (EUCS) Di Universitas Al Washliyah Medan - Manao, Ibnu Afandi; Sarif, Muhammad Irfan; Helmandi, Asrul; Pohan, Muhammad Zainal Arifin; Sumiran, Sumiran (Journal of Computer Science and Information System(JCoInS), 2026)
This study analyzes the service quality of the Integrated Academic System of Universitas Al Washliyah (SATUVA) and its effects on user satisfaction and productivity at Universitas Al Washliyah Medan. Using the End‑User Computing Satisfaction (EUCS) method, a quantitative survey was conducted among lecturers, administrative staff, and students to measure dimensions such as content, accuracy, format, ease of use, timeliness, and technical support. Statistical analyses included reliability testing, correlation, and regression to examine relationships between service quality, satisfaction, and productivity. Results indicate that SATUVA’s service quality significantly influences user satisfaction, and satisfaction mediates the effect of service quality on user productivity. Findings highlight the need to improve interface design, data accuracy, user training, and support responsiveness to enhance the system’s effectiveness. Recommendations are offered for continuous development to support the university’s academic and administrative performance.